2001
DOI: 10.1007/s004250100543
|View full text |Cite
|
Sign up to set email alerts
|

Circular F-actin bundles and a G-actin gradient in pollen and pollen tubes of Lilium davidii

Abstract: The distribution of and relationship between F-actin and G-actin were investigated in pollen grains and pollen tubes of Lilium davidii Duch. using a confocal laser scanning microscope after fluorescence and immunofluorescence labeling. Circular F-actin bundles were found to be the main form of microfilament cytoskeleton in pollen grains and pollen tubes. Consistent with cytoplasmic streaming in pollen tubes, there were no obvious F-actin bundles in the 10- to 20-microm tip region of long pollen tubes, only a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 55 publications
3
28
0
Order By: Relevance
“…To further confirm the MG132-induced disruption of the cytoskeleton, confocal microscopy was used to visualize the cytoplasmic streaming in pollen tubes, a phenomenon that depends on intact cytoskeleton elements, especially actin microfilaments (Taylor and Hepler, 1997;Li et al, 2001;Justus, et al, 2004). As shown in Figure 10A (see also Supplemental Video 1), cytoplasm in control tubes streams in a fountain pattern or, rarely, in a reverse fountain pattern, similar to a previous report in Picea abies pollen tubes (Justus, et al, 2004).…”
Section: Mg132 Treatment Disrupts Cytoskeleton Organization and Cytopsupporting
confidence: 76%
See 1 more Smart Citation
“…To further confirm the MG132-induced disruption of the cytoskeleton, confocal microscopy was used to visualize the cytoplasmic streaming in pollen tubes, a phenomenon that depends on intact cytoskeleton elements, especially actin microfilaments (Taylor and Hepler, 1997;Li et al, 2001;Justus, et al, 2004). As shown in Figure 10A (see also Supplemental Video 1), cytoplasm in control tubes streams in a fountain pattern or, rarely, in a reverse fountain pattern, similar to a previous report in Picea abies pollen tubes (Justus, et al, 2004).…”
Section: Mg132 Treatment Disrupts Cytoskeleton Organization and Cytopsupporting
confidence: 76%
“…It has long been appreciated that AFs control cytoplasmic streaming and hence the transport of secretory vesicles (Taylor and Hepler, 1997;Li et al, 2001;Justus et al, 2004). More recent evidence indicates that, in addition to actomyosin-driven streaming, actin polymerization itself also contributes to pollen tube growth, either as a force generator (Balu拧ka and Volkmann, 2002) or as an organizer of the apical cytoplasm ).…”
Section: Discussionmentioning
confidence: 99%
“…When the pollen tube elongates, the actin filaments organize into longer bundles and gradually enter the emerging tube (Cai et al, 1997). When the pollen tube grows, the actin cytoskeleton form thick bundles parallel to the pollen tubes (Li et al, 2001). In our research, such dynamic organization of actin arrays occurred in both treated and control pollen grains, but the actin cytoskeleton in pollen implanted by 5.2 脳 10 15 ions/cm 2 Ar + organized much earlier than that in the control pollen, and the reorganization of the actin cytoskeleton in pollen implanted with 9.1 脳 10 15 ions/cm 2 Ar + was comparatively slower than that in the control pollen.…”
Section: Discussionmentioning
confidence: 99%
“…The first and most parsimonious explanation is that actin bundles control cytoplasmic streaming and hence the delivery of secretory vesicles essential for growth (Wang et al, 2006;Samaj et al, 2006). Li et al (1998) found that the microfilaments just extended to the region 10~20 渭m from the pollen tube apex, while cytoplasmic streaming also changes in direction at this region. Additional support for a role of actin microfilaments in intracellular motility comes from studies using the fungal toxin cytochalasin B.…”
Section: Discussionmentioning
confidence: 99%
“…The actin cytoskeleton is a highly organized and dynamic structure present in all eukaryotic cells, where it plays a central role and is involved in numerous cellular processes, including intracellular transport, cell growth, cell division, cytoplasmic streaming, organelle positioning, and cell-to-cell communication (15)(16)(17)(18)(19). For such processes, a regulatory system is required that contains actin filaments and actin-binding proteins (ABPs) that directly interact with G-actin and/or F-actin to promote the nucleation, polymerization, depolymerization, stabilization, severing, capping, bundling, and cross-linking of actin filaments (20 -23).…”
Section: Vacuolar Hmentioning
confidence: 99%